Words, words. They're all we have to go on: Image finding without the pictures. - Brown, Stephen (Digital Scholarship in the Humanities, 2016)
This article describes a Recommendation System to help photographic historians make connections between widely dispersed and previously unrelated records of photographs held in different heritage institutions, and demonstrates how it has been used to rediscover images of exhibits from the Royal Photographic Society annual exhibitions of over 120 years ago. While the surviving exhibition catalogues are a rich information source, they are largely devoid of illustrations of the exhibits. The FuzzyPhoto project has developed techniques for analyzing a corpus of more than 1.4 million historical photographic records across different galleries, libraries, archives, and museums, in order to identify similarities between them and used the results to offer visitors to those sites links to potentially related items at other sites, thus creating a web of interconnections between them. The article describes techniques used for data acquisition, cleaning, integration, semantic- based data mining, approximate reasoning, and fuzzy algorithm-based similarity metrics. It compares the approach described here with manual searches and more sophisticated computational methods such as linked data and concludes that FuzzyPhoto is an effective method for dealing with the realities of messy collection records that could be extended to other types of archival objects such as paintings, maps, and textiles where record matching is required.